The Class Action As Political Theory - Martin H. Redish; Clifford W. Berlow (Washington University Law Review, 2007)
We have two goals in this Article. Initially, we seek to alter the nature of the class action debate, by expressly inserting the perspective of political theory. Recognizing how the modern class action is structured may have significant consequences for the foundations of normative political theory, we hope to remove the theoretical superficiality that has characterized much of the modern scholarly debate concerning class actions. While on occasion that debate has touched on questions of political theory, those references are generally superficial or misguided. At the very least, then, we hope to establish that acceptance of one or the other of the scholarly models of the class action necessarily brings with it significant political baggage. Second, we hope to convince the reader that, when viewed from this perspective, all class action models that have been proposed to this point should be rejected because they ignore, undermine, or dilute fundamental notions of process-based individual autonomy.
Keywords: Political philosophy; Class actions (Civil procedure); Class action – Political aspects